Pengaruh Motivasi Kerja, Pengalaman Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan - Idrus, Muhammad Ikram; Idrus, Muhammad Ishlah; Ismail, Muhammad (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
This research aims to analyze the influence of work motivation, work experience, and work environment on employee performance in the context of management. The data used are the results of research from 20 economic journals investigated, as well as previous journal reviews to enhance data accuracy. The research findings indicate that work motivation, which includes intrinsic and extrinsic factors, significantly impacts employee performance. Intrinsic factors, such as the drive to achieve organizational goals, sense of responsibility, and recognition of achievements, as well as extrinsic factors, such as financial incentives, influence employees' work motivation. Employees who feel motivated intrinsically and extrinsically tend to demonstrate better performance. In addition to motivation, work experience also influences employee performance. Work experience enables employees to gain the knowledge and skills needed to perform tasks effectively. The more experienced someone is, the more competent they are in performing their tasks. The work environment also plays a crucial role in determining employee performance. Factors such as cleanliness, comfort, adequate facilities, good communication, and positive interpersonal relationships affect employee productivity. Employees working in a supportive environment tend to demonstrate better performance and dedication to their work. These findings emphasize the importance of human resource management in improving employee performance and productivity. By understanding the factors that influence work motivation, work experience, and work environment, companies can create a supportive environment for overall organizational growth and success. The practical implications of this research are that human resource managers need to consider these factors in designing motivation programs, employee development, and workplace design. In the context of increasingly fierce business competition, understanding and optimizing these factors can be a competitive advantage for companies. By implementing the right strategies in managing work motivation, work experience, and work environment, companies can improve employee performance and productivity, ultimately supporting the achievement of organizational goals.